Influence of soil γ-irradiation and spiking on sorption of p,p'-DDE and soil organic matter chemistry - Škulcová, Lucia; Scherr, Kerstin E; Chrást, Lukáš; Hofman, Jakub; Bielská, Lucie (Ecotoxicology and environmental safety, 2018)
The fate of organic chemicals and their metabolites in soils is often investigated in model matrices having undergone various pre-treatment steps that may qualitatively or quantitatively interfere with the results. Presently, effects associated with soil sterilization by γ-irradiation and soil spiking using an organic solvent were studied in one freshly spiked soil (sterilization prior to contamination) and its field-contaminated (sterilization after contamination) counterpart for the model organic compound 1,1-Dichloro-2,2-bis(4-chlorophenyl)ethene (p,p'-DDE). Changes in the sorption and potential bioavailability of spiked and native p,p'-DDE were measured by supercritical fluid extraction (SFE), XAD-assisted extraction (XAD), and solid-phase microextraction (SPME) and linked to qualitative changes in soil organic matter (SOM) chemistry measured by diffuse reflectance infrared Fourier-transform (DRIFT) spectroscopy. Reduced sorption of p,p´-DDE detected with XAD and SPME was associated more clearly with spiking than with sterilization, but SFE showed a negligible impact. Spiking resulted in an increase of the DRIFT-derived hydrophobicity index, but irradiation did not. Spectral peak height ratio descriptors indicated increasing hydrophobicity and hydrophilicity in pristine soil following sterilization, and a greater reduction of hydrophobic over hydrophilic groups as a consequence of spiking. In parallel, reduced sorption of p,p´-DDE upon spiking was observed. Based on the present samples, γ-irradiation appears to alter soil sorptive properties to a lesser extent when compared to common laboratory processes such as spiking with organic solvents.
Keywords: záření gama; SFE; dichlordifenyldichlorethylen; Gamma Rays; mikroextrakce na pevné fázi; γ-irradiation; Soil Pollutants; Biological Availability; Solvents; Adsorption; Soil spiking; látky znečišťující půdu; biologická dostupnost; Dichlorodiphenyl Dichloroethylene; SPME; rozpouštědla; XAD; DDE; Sorption; Solid Phase Microextraction; Soil sterilization; Soil; půda; adsorpce